Women and men with stable coronary artery disease have similar clinical outcomes: insights from the international prospective CLARIFY registry - Steg, Ph Gabriel (Oxford University Press, 2012)
AIMS: Men and women differ in terms of presentation and management in coronary artery disease (CAD). Whether these differences translate into different clinical outcomes in stable CAD is unclear. We analysed data from the international prospective CLARIFY registry to compare cardiovascular clinical outcomes in men and women with stable CAD. METHODS AND RESULTS: We analysed 1-year outcomes in 30 977 outpatients with stable CAD [23 975 (77.4%) men; 7002 (22.6%) women]. Women were older than men, more likely to have hypertension and diabetes, and less likely to exercise or smoke. They had more frequent angina, but were less likely to have undergone diagnostic non-invasive testing or coronary angiography. Women received less optimized treatment for stable CAD. One-year outcomes were similar for men and women for the composite of cardiovascular death, non-fatal myocardial infarction, or stroke [adjusted rates 1.7 vs. 1.8%, respectively, odds ratio (OR) 0.93, 95% confidence interval (CI) 0.75–1.15]; all-cause death (adjusted 1.5 vs. 1.6%, OR: 0.91, 95% CI: 0.72–1.13); fatal or non-fatal myocardial infarction (adjusted 1.0 vs. 0.9%, OR: 0.81, 95 CI: 0.60–1.08); and cardiovascular death or non-fatal myocardial infarction (adjusted 1.4 vs. 1.4%, OR: 0.89, 95% CI: 0.70–1.12). Fewer women underwent revascularization (2.6 vs. 2.2%, OR: 0.77, 95% CI: 0.64–0.93), although appropriateness was not analysed. CONCLUSION: The risk profiles of women and men with stable CAD differ substantially. However, 1-year outcomes were similar. Fewer women underwent revascularization. Further research is needed to better understand gender determinants of outcome and devise strategies to minimize bias in the management and treatment of women.